Necroptotic, autophagic and other non-apoptotic mechanisms - Ashkenazi, Avi; Wells, James A.; Yuan, Junying (Regulated cell death, 2014)
This volume covers research methods in apoptosis focusing on the important areas of intrinsic pathway, extrinsic pathway, caspases, cellular assays and post-apoptotic effects and model organisms; as well as topics on necroptosis and screening approaches
Includes bibliographical references and indexes. - Print version record
Keywords: Electronic books; Autophagie; Nekrose